Project Based Learning in Fiqh Learning and Its Effect on Students' Higher Order Thinking Skills - Ramadani, Laili; Kardi, Juliwis; Hidayat, Taufik; Putra, Adi; Abdi, Hamdani (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2024)
This study aims to determine the project-based learning model in learning Fiqh and its effect on the achievement of Higher Order Thinking Skills (HoTS) of students at the madrasah tsanawiyah level. This type of research is a quantitative true experimental design. This study used two sample classes, namely the control class and the experimental class. The experimental class was treated using project-based learning. While in the control class without using project-based learning in learning. At the end of the study, the experimental and control classes were given a test to see the achievement of students' Higher Order Thinking Skills (HoTS). The research design used was randomize control group posttest only design, the sample was selected using purposive sampling technique from the study population, namely 21 students in the experimental class who used project-based learning model in Fiqh learning and 21 students in the control class who used conventional learning. To collect data from the sample, a final test was used using Higher Order Thinking Skills (HoTS) quality questions. The data was analyzed using the SPSS window 18.0 program. From the data analysis, the average HoTS value of the experimental class was 94.28 and the average value of the control class was 82.95. From the results of hypothesis testing obtained t count of 9.568 with t table of 1.684. The condition is that H0 is rejected if tcount> ttable. So it can be concluded that the application of project-based learning model in learning Fiqh affects the achievement of Higher Order Thinking Skills (HoTS) of students at the madrasah tsanawiyah level.